Nursing of a patient with furuncle of the nose treated with Tradition Chinese Medicine collapse stains (中药塌渍治疗鼻疖1例的护理体会) - WANG Dongmei (王冬梅); ZHANG Li (张丽); HE Zihao (何子豪); XIAO Hong (肖红); ZHU Xinyu (朱鑫宇); WANG Xing (王星) (Association of Integrative Nursing, 2023)
This paper summarized the nursing measures of a patient with furuncle of the nose treated with Tradition Chinese Medicine (TCM) collapse stains. The nursing assessment, application method and cautions of collapse stains, compostion of Chinese herbs, dietary guidance and psychological intervention were reviewed. Through the active intervention of the external treatment of Tradition Chinese Medicine, the level of nasal boils decreased, pain was relieved, and good results were achieved. (本文总结1例中药塌渍治疗鼻疖患者的护理经验, 包括护理评估、中药塌渍操作方法、药方组成、注意事项以及饮食指导、心理干预等护理措施。基于辨证施护理念, 通过中药塌渍外治法积极干预, 并辅以相关护理措施, 能有效改善患者鼻疖症状, 减轻疼痛。)